PENERAPAN ETIKA BISNIS ISLAM DALAM PENJUALAN ONLINE DI MEDIA SOSIAL TIKTOK - Muzanni Muzanni (Department of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2025)
This study aims to analyze the marketing practices of Muslim entrepreneurs on TikTok and their alignment with Islamic business ethics. The main focus of this research is to examine how businesses promote halal products on social media and how well they adhere to principles of honesty and fairness in digital marketing. A qualitative research method with a descriptive approach was used, analyzing TikTok videos related to halal products. The findings indicate that although there are efforts to adhere to sharia principles, many entrepreneurs prioritize material gain without fully considering Islamic ethical values. The research also found that the use of Muslim influencers can increase consumer trust, but it also raises concerns about the integrity of the information conveyed. The findings are expected to contribute to the development of sharia marketing on digital platforms.